Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2307/j.ctvckq7qf
|View full text |Cite
|
Sign up to set email alerts
|

The Master Equation and the Convergence Problem in Mean Field Games

Abstract: The paper studies the convergence, as N tends to infinity, of a system of N coupled Hamilton-Jacobi equations, the Nash system. This system arises in differential game theory. We describe the limit problem in terms of the so-called "master equation", a kind of second order partial differential equation stated on the space of probability measures. Our first main result is the well-posedness of the master equation. To do so, we first show the existence and uniqueness of a solution to the "mean field game system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
511
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(517 citation statements)
references
References 53 publications
5
511
1
Order By: Relevance
“…In this section, we present quantized solutions for Problems 1 and 2 to reduce the complexity in space for dynamic programs (25) and (42) in Theorems 2 and 4, respectively.…”
Section: Quantization Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we present quantized solutions for Problems 1 and 2 to reduce the complexity in space for dynamic programs (25) and (42) in Theorems 2 and 4, respectively.…”
Section: Quantization Resultsmentioning
confidence: 99%
“…The optimal strategy of Theorem 2 can be implemented in a distributed manner since every agent can independently compute the dynamic program (25) and observe the deep state. 2 According to (26), for any k ∈ K, i ∈ N k and t ∈ N T , the action (role) of agent i of sub-population k at time t is determined by three factors: (a) global law ψ t that depends on the agents' dynamics, per-step cost, and underlying probability distributions; (b) deep state d t that provides the statistical information on the states of agents, and (c) local state x i t that is private information for agent i and unknown to others.…”
Section: B Admissible Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In such games, the individual agents have minimal impact of the overall outcome of the game and so the agents track a mean distribution of states of other agents rather than their actual states. MFGs is an excellent and a tractable model to study large population dynamic games of incomplete information, and has been shown to be a good approximation of Nash equilibrium (or MPE) of the original game as the number of players grow large (for instance see [7], [8], [9], [10], [11] and references therein).…”
Section: A Relevant Literaturementioning
confidence: 99%